'Here quietude is linked with stillness': Winnicott's Silent Core of the Self and Aesthetic Experience. (29th November 2022) - Pihlaja, Eeva
Abstract : In his paper 'Communicating and not communicating leading to a study of certain opposites' (1963), Donald Winnicott suggests that there is a silent, non‐communicating area of experience at the core of the self. Poetic expression takes a prominent role in the text. In this article, I concentrate on the aesthetic dimension of Winnicott's text and use it to explore the role of aesthetic experience in the development of self‐experience. I suggest that the paper's aesthetic dimension—form, quality and structure—expresses essential characteristics of the core of the self and the mature self's communication with it. I furthermore suggest that Winnicott, by use of poetic expression, offers the idea that the core, defined here as pre‐reflective experience, can be approached through aesthetic means. Building on George Hagman and Giuseppe Civitarese, I argue that aesthetic experience creates a bridge between pre‐reflective and reflective aspects of self‐experience and thus contributes to the integration of self. I suggest that forming a connection with the core can be seen as an aesthetic act where the intention is not to transform pre‐reflective experience into reflective. Since aesthetic experience includes reflection, the effort to represent the core of the self remains paradoxical.